Pelatihan Komposting Remaja Masjid Raudhatul Islamiyah Kabupaten Kubu Raya - Ulli Kadaria; Aini Sulastri; Winardi (Universitas Mathla'ul Anwar Banten, 2022)
COMPOSTING TRAINING FOR YOUTH AT RAUDHATUL ISLAMIYAH MOSQUE KUBU RAYA REGENCY. Youth of Raudhatul Islamiyah Mosque is one of the youth Muslim organizations who live in Central Java Village, Ambawang District, Kubu Raya Regency. Even though they are based on Islam, mosque youth are not only engaged in religious activities. Several activities have been carried out at that location and the participation of the youth of the mosque is very good, this is proven by the well-maintained tools that have been given and the routine activities that are carried out in mutual cooperation. In previous activities, community services were also carried out in the form of socializing the sorting of organic and inorganic waste and providing composting tools on a small scale, but the interest of mosque youth in processing waste, especially organic waste, needs to be facilitated. In this activity, socialization and training on composting were carried out, as well as the provision of composting equipment on a large scale. Mosque youth are actively involved in socialization and training activities. After the socialization, training, and mentoring activities, it is hoped that the youth of the mosque can develop the knowledge that has been obtained for a wider scope and can be applied in their respective neighborhoods so as to reduce the volume of organic waste.